A new perspective on Alzheimer’s disease: microRNAs and circular RNAs - Abidin, Shahidee Zainal; Mat Pauzi, Nurul Asykin; Mansor, Nur Izzati; Mohd Isa, Nurul Iffah; Hamid, Adila A. (Frontiers in Genetics, 2023)
microRNAs (miRNAs) play a multifaceted role in the pathogenesis of Alzheimer’s disease (AD). miRNAs regulate several aspects of the disease, such as Aβ metabolism, tau phosphorylation, neuroinflammation, and synaptic function. The dynamic interaction between miRNAs and their target genes depends upon various factors, including the subcellular localization of miRNAs, the relative abundance of miRNAs and target mRNAs, and the affinity of miRNA-mRNA interactions. The miRNAs are released into extracellular fluids and subsequently conveyed to specific target cells through various modes of transportation, such as exosomes. In comparison, circular RNAs (circRNAs) are non-coding RNA (ncRNA) characterized by their covalently closed continuous loops. In contrast to linear RNA, RNA molecules are circularized by forming covalent bonds between the 3′and 5′ends. CircRNA regulates gene expression through interaction with miRNAs at either the transcriptional or post-transcriptional level, even though their precise functions and mechanisms of gene regulation remain to be elucidated. The current stage of research on miRNA expression profiles for diagnostic purposes in complex disorders such as Alzheimer’s disease is still in its early phase, primarily due to the intricate nature of the underlying pathological causes, which encompass a diverse range of pathways and targets. Hence, this review comprehensively addressed the alteration of miRNA expression across diverse sources such as peripheral blood, exosome, cerebrospinal fluid, and brain in AD patients. This review also addresses the nascent involvement of circRNAs in the pathogenesis of AD and their prospective utility as biomarkers and therapeutic targets for these conditions in future research.